The Influence of Employee Engagement on Work Productivity: A Case Study on the Creative Industry in the Digitalization Era in Mataram City - Bagea, Arfin; M. Budihard, Andi; Adwi; Efendi, Haerul; Yasin, Muh. (Journal of Management, 2024)
This study aims to analyze the effect of employee engagement, measured through the dimensions of Vigor, Dedication, and Absorption, on Work Productivity in the context of the creative industry in the digitalization era. This study used a quantitative approach with a correlational design, involving 100 employees from companies in the creative industry. Data were collected using a questionnaire based on the Utrecht Work Engagement Scale (UWES) and processed through linear regression analysis using statistical software. The results of the analysis showed that the overall regression model was significant (F = 36.415, p < 0.05), with an R Square value = 0.532, meaning 53.2% of the variability in Work Productivity can be explained by the three dimensions of employee engagement. Individually, only the Vigor dimension has a significant effect on Work Productivity (B = 0.388, p < 0.05), while the Dedication (p = 0.114) and Absorption (p = 0.341) dimensions show no significant effect. These findings indicate that employee energy and vigor play a key role in driving productivity in a dynamic creative work environment.